THE EFFECT OF LIQUIDITY, PROFITABILITY, AND CAPITAL STRUCTURE ON DIVIDEND POLICY IN PROPERTY AND REAL ESTATE SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE PERIOD 2019–2023 - Silvia Ananda; Wahyuddin; Marzuki; Ghazali Syamni (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This study aims to analyze the effect of liquidity, profitability, and capital structure on dividend policy in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. The research sample consists of 50 companies with a total of 250 observations over five years, selected using a purposive sampling method. Secondary data were obtained from the companies’ annual financial reports accessed through the official IDX website. The dependent variable in this study is dividend policy, proxied by the Dividend Payout Ratio (DPR) in the form of a dummy variable, while the independent variables include liquidity (Current Ratio), profitability (Return on Assets), and capital structure (Debt to Equity Ratio). Data analysis was performed using logistic regression. The results show that profitability has a positive and significant effect on dividend policy, while liquidity and capital structure do not have a positive and significant effect on dividend policy in property and real estate sector companies listed on the IDX for the period 2019–2023.